Death Penalty for Corruption Crimes Reviewed From a Human Rights Perspective - Sujono, Sujono; Dirgantini, Marissa Kemala; Atmoko, Dwi (Ridwan Institute, 2024)
Prevention & eradication of criminal acts of corruption in Indonesia has been very intensively implemented because corruption in Indonesia is now so rampant, acute, and systemic. The existence of firm and harsh criminal sanctions has a very important role in the process of eradicating corruption. In Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes or what is called the PTPK Law, there is a juridical space that can be used to impose death penalty sanctions on perpetrators of criminal acts of corruption, namely in Article 2 paragraph (2) The PTPK Law stipulates that if the criminal act of corruption as intended in paragraph (1) is committed under certain circumstances, the death penalty can be imposed.